2014
DOI: 10.3389/fpsyg.2014.00914
|View full text |Cite
|
Sign up to set email alerts
|

Making and monitoring errors based on altered auditory feedback

Abstract: Previous research has demonstrated that altered auditory feedback (AAF) disrupts music performance and causes disruptions in both action planning and the perception of feedback events. It has been proposed that this disruption occurs because of interference within a shared representation for perception and action (Pfordresher, 2006). Studies reported here address this claim from the standpoint of error monitoring. In Experiment 1 participants performed short melodies on a keyboard while hearing no auditory fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…Finally, assessment of the questionnaires filled out by the participants revealed that they overestimated the number of pitch errors due to the presence of AAF, an outcome that has been reported in a previous behavioral study [Pfordresher and Beasley, 2014]. The subjective number estimate of self-produced errors per sequence type was 19 (1), whereas the number of self-produced errors was 15 (2), and the difference was significant (P 5 0.016, PS dep 5 0.80).…”
Section: Error Ratessupporting
confidence: 63%
See 1 more Smart Citation
“…Finally, assessment of the questionnaires filled out by the participants revealed that they overestimated the number of pitch errors due to the presence of AAF, an outcome that has been reported in a previous behavioral study [Pfordresher and Beasley, 2014]. The subjective number estimate of self-produced errors per sequence type was 19 (1), whereas the number of self-produced errors was 15 (2), and the difference was significant (P 5 0.016, PS dep 5 0.80).…”
Section: Error Ratessupporting
confidence: 63%
“…Until now almost all neuroimaging studies investigating the effects of AAF did not use pitch alterations that interfered with the serial order of the actions in the sequence [Chang el al, 2013; Maidhof et al, ; Tourville et al, ; Zarate and Zatorre, ]. One notable exception is the functional magnetic resonance imaging (fMRI) study by Pfordresher and colleagues (), which used six different kinds of AAF after their pianist subjects undertook initial training on piano melodies. This study revealed an involvement of the premotor cortex in processing delayed auditory feedback (temporal shift), and an engagement of the cerebellum and ACC in processing serially shifted feedback.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, the relationship between executive control resources and adaptation was explored in one previous study. Testing the assumption that processing of altered auditory feedback (conflict detection) involves executive control, Pfordresher and Beasley ( 2014 ) had participants perform an altered auditory feedback task while simultaneously performing a secondary executive control task. The primary task was to perform piano melodies on a keyboard while hearing, in the critical condition, auditory feedback altered in pitch on some trials.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the size of the pitch shift responses was correlated with pitch matching accuracy rather than with performance on change detection with small pitch differences. In addition, recent data also showed an inverse correlation between note accuracy and perturb-ability - i.e., poor pitch singers were less affected by altered auditory feedback (Pfordresher & Beasley, 2014), again providing support for an unconscious pathway for pitch modulation in singing that is dissociable from the conscious route that is used for detection of fine-grained pitch changes.…”
Section: Disruption Of Singing: Insights From Congenital Amusia and Pmentioning
confidence: 92%